3D Cooperative Multiplayer Online Game Design as Introduction to Gobak Sodor Traditional Sports Game : Multimedia Development Life Cycle (MDLC) - Salimi, Moh; Maryono, Dwi; Budiyanto, Cucuk Wawan; Aristyagama, Yusfia Hafid (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This research aims to develop a design for a 3D Cooperative Multiplayer Online Game to introduce the traditional sport of â€œGobak Sodorâ€ to students. This research method used research and development based on the Multimedia Development Life Cycle (MDLC) steps consisting of concept, design, material collecting, assembly, and testing. Expert Judgement was required to evaluate and validate the developed design by considering various aspects. The testing conducted by media experts resulted in a score of 83,93%. The result of this study indicated that the proposed design falls into the highly feasible category. The results of this research imply that this media can be used to preserve traditional game culture.